IMPROVING THE EFFICIENCY OF CLEANING SMALL TRASH FROM SEED COTTON IN THE CLEANING PROCESS (Multidisciplinary Journal of Science and Technology, 2024)
the article deals with the development of high-efficiency cotton processing technology, the rational arrangement of working bodies, and the determination of movement trajectories of cotton components to ensure high cleaning efficiency.